If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 17 = -24 + 6x Reorder the terms: 17 + 6x = -24 + 6x Add '-6x' to each side of the equation. 17 + 6x + -6x = -24 + 6x + -6x Combine like terms: 6x + -6x = 0 17 + 0 = -24 + 6x + -6x 17 = -24 + 6x + -6x Combine like terms: 6x + -6x = 0 17 = -24 + 0 17 = -24 Solving 17 = -24 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 6d-2=40 | | -22=-6w+2(w+5) | | 50-3x=6x+17 | | 0=-x-3 | | p(3p+2)=0 | | 13-7x=109-28x | | (4x-6)+(5x+7)= | | =(4x-6)+(5x+7) | | 17+2n=87 | | (b+4)(2b-5)=0 | | X-2(-1)=6 | | 4(2y+3)-5(y+3)= | | x*2x+x*10= | | 58-2x=10x+22 | | 118-6x=10x-22 | | .38x+.44(7)=.40(x+7) | | 116-3x=15x+24 | | 5x+7=-38-10x | | 8+3x=128 | | -12-9x=27-16x | | 95-3x=4x+11 | | -12m-37(12n+8m)= | | -7-7x=8x+23 | | 25x-1=65 | | 4(3r-2)=-3(r+7) | | 5x+5=95-5x | | 6x+7=-121-10x | | 8x+6=30 | | 3p(2p-4)-2p(3p+4)= | | 1=35-5(x+3) | | 104-6x=3x+5 | | 2x-1=9x-78 |